Effect of carbonic anhydrase and urease on bacterial Calcium carbonate precipitation - J. NEENA PRIYA; M. KANNAN (International Journal of Pharma and Bio Sciences, 2017)
There are number of diverse microbial species complementing the carbonate precipitation in different natural environment like soil, ocean and in geological formation. Even some common soil bacteria can precipitate calcium carbonate under appropriate conditions. Bacteria can serve as a nucleus of carbonate precipitation under the influence of two essential enzymes such as Urease and Carbonic anhydrase. Urease helps in mineralization of calcium carbonate, by hydrolysing urea into ammonium and carbonate in the environment. Carbonic anhydrase is an enzyme that catalyses reversible hydration of co2 in different microorganisms and plays an important role in carbonate precipitation. In this present study, four strains of Bacillus and five strains of Pseudomonas were tested for its urease and carbonic anhydrase activity that significantly showed the capability of these bacterial strains for calcium carbonate precipitation.